Origem e dinâmica da salinidade dos aquíferos cristalinos fraturados da região semiárida Cearense (Brasil) - Kreis, Marjorie Beate (2021)
The high levels of groundwater salinity of groundwater observed in the crystalline basement rocks in semi-arid NorthEastern Brazil stimulated research since the 1960s. The present study uses hydrodynamic (monthly and hourly piezometric data) and hydrochemical (Electrical Conductivity EC, major ions, Cl/Br, trace elements) methods in addition to a wide analytical investigation based on a multi-tracer approach (180, 2H, 3H, 14C, CFC, SF6) to identify the origin of the salts, characterize the recharge and circulation processes, and determine the mechanisms that lead to the salinization of the groundwater contained in the crystalline rocks of semi-arid regions. The piezometric survey revealed the high reactivity of the aquifer to precipitation and suggests that the recharge of the aquifers depends on significant rainy events that may have favored runoff and surface water accumulation. Indeed, the investigation carried out with more than 500 stable isotopes analyses (monthly and/or daily data) showed that this recharge occurs through direct infiltrations, with a more or less significant proportion of indirect infiltration of evaporated surface water. Even if there is no direct relationship between the total annual precipitation and the aquifer’s recharge, this study showed that the seasonal recharge is weak and of the order of 1 to 3% of the annual rainfall (≈7 to 21 mm/year). The crystalline aquifers are characterized by low transmissivities (median value around de 3.10-6 m²/s), low porosities (< 0,5%), low hydraulic conductivity (in the order of a few centimeters per day) and a strong lateral compartmentalization (absence of regional flow). The multi-tracer analysis highlighted that groundwater residence time is short (from a few decades to hundreds of years, with a large contribution of post-1950 water) and that the circulation processes are fast. However, this estimate is an apparent age resulting from complex circulation flow patterns in fractured aquifers, because flows are essentially composed of seasonal vertical infiltration flows (direct and indirect) and horizontal transfers of longer transit time (infiltration before the 1960s). Thus, in addition to a strong spatial heterogeneity, a strong vertical stratification is observed in the fractured crystalline basement (increase of the water’s EC with the fracture’s depth). Waters in the study are characterized by high chlorides concentrations (up to 5 g/L) and essentially show mixed-chloride or sodium-chloride facies, with EC ranging from 890 to 19300 µS/cm. The chemical study suggests that the waters, originally bicarbonated, became chlorinated due to the dissolution and leaching of salts (as calcite, dolomite, gypsum, halite and probably MgCl2) that precipitated in the soil, in the unsatured zone and/or in the sediments, due to the strong evapotranspiration rates of rainfall and surface waters. However, simulations have shown that climatic aridity and strong evapotranspiration rates cannot lead to a strong salinization of the groundwater over a period of time of the order of hundreds of years, but to chloride concentrations in the order of a few tens of mg/L, 100 to 200 mg/L at most. Thus, simulations showed that the only factor that is capable of causing a strong salinization of the aquifer (with concentrations of the order of g/L) is the presence of subterraneous endorrheic conditions (decrease in the piezometric level) due to the transpiration of the groundwater by the deep roots of the Caatinga tree layer, with an evapotranspiration rate equivalent to the total annual recharge, which implies that there is no longer direct relationship between the apparent age of the waters and the accumulation of salts in the aquifers. Simulations suggests that aquifers would be in a current dynamic of desalination due to the deforestation of the Caatinga tree layer, and this, despite the influence of the infiltration of evaporated water in the recharge processes.